Impaired systemic tetrahydrobiopterin bioavailability and increased oxidized biopterins in pediatric falciparum malaria : association with disease severity - Granger, Donald L. (2015)
Decreased bioavailability of nitric oxide (NO) is a major contributor to the pathophysiology of severe falciparum malaria. Tetrahydrobiopterin (BH4) is an enzyme cofactor required for NO synthesis from L-arginine. We hypothesized that systemic levels of BH4 would be decreased in children with cerebral malaria, contributing to low NO bioavailability. In an observational study in Tanzania, we measured urine levels of biopterin in its various redox states (fully reduced [BH4] and the oxidized metabolites, dihydrobiopterin [BH2] and biopterin [B0]) in children with uncomplicated malaria (UM, n = 55), cerebral malaria (CM, n = 45), non-malaria central nervous system conditions (NMC, n = 48), and in 111 healthy controls (HC). Median urine BH4 concentration in CM (1.10 [IQR:0.55–2.18] μmol/mmol creatinine) was significantly lower compared to each of the other three groups — UM (2.10 [IQR:1.32–3.14];p<0.001), NMC (1.52 [IQR:1.01–2.71];p = 0.002), and HC (1.60 [IQR:1.15–2.23];p = 0.005). Oxidized biopterins were increased, and the BH4:BH2 ratio markedly decreased in CM. In a multivariate logistic regression model, each Log10-unit decrease in urine BH4 was independently associated with a 3.85-fold (95% CI:1.89–7.61) increase in odds of CM (p<0.001). Low systemic BH4 levels and increased oxidized biopterins contribute to the low NO bioavailability observed in CM. Adjunctive therapy to regenerate BH4 may have a role in improving NO bioavailability and microvascular perfusion in severe falciparum malaria.